Indirubin modulates CD4+ T‐cell homeostasis via PD1/PTEN/AKT signalling pathway in immune thrombocytopenia. Issue 3 (4th January 2019) - Zhao, Yajing; Han, Panpan; Liu, Lei; Wang, Xiaojie; Xu, Pengcheng; Wang, Haoyi; Yu, Tianshu; Sun, Yunqi; Li, Lizhen; Sun, Tao; Liu, Xinguang; Zhou, Hai; et al.
Abstract: Immune thrombocytopenia (ITP) is an acquired autoimmune disease characterized by an immune mediated decrease in platelet number. Disturbance of CD4 + T‐cell homeostasis with simultaneous decrease of CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) as well as unrestricted proliferation and activation of peripheral CD4 + effector T cells underpin the pathophysiology of ITP. Indirubin is an active ingredient of a traditional Chinese herb called Indigofera tinctoria L. which is clinically used for the treatment of ITP patients. Whether indirubin targets the Tregs/effector T cell‐axis to restore platelet number is unknown. In our in vitro studies, Indirubin could significantly enhance the number and function of Tregs and meanwhile dampen the activation of effector T cells in a dose‐dependent manner. Indirubin was observed to restore the expression of programmed cell‐death 1 (PD1) and phosphatase and tensin homolog (PTEN) on the CD4 + T cells of ITP patients, leading to the subsequent attenuation of the AKT/mTOR pathway. Furthermore, these observations were recapitulated in an active murine model of ITP with a prominent platelet response. Thus, our results identified a potentially novel mechanism of the therapeutic action of indirubin in the treatment of ITP through regulating the homeostasis of CD4 + T cells in a PD1/PTEN/AKT signalling pathway.